USE OF SPATIAL ANALYSIS TOOLS AND CAPABILITY OF GEOINFORMATION SYSTEMS FOR ASSESSMENT OF THE STATE OF UNDERGROUND WATERS - Ostroukh, О.; Chomko, D.; Ostroukh, Ostroukh; Pidlisetska, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The results of the study of the ecological-hydrogeochemical state of the underground waters of the Chop-Mukachevo basin and the identification of its spatio-temporal changes in the chemical composition using GIS facilities are presented. The methodology for processing the initial hydrogeological data on the basis of geographic information technologies has been improved and tested on the example of spatio-temporal changes in the indicators of chemical composition. A specialized geoinformation database of the chemical composition of groundwater has been created. The evaluation of spatio-temporal patterns of changes in the chemical composition using statistical analysis, cartographic modeling, and spatial analysis in GIS, identified areas with increased salinity and hardness of groundwater. Based on an integrated approach, zoning was performed and the current hydrogeochemical state of the groundwater resources of the study area was evaluated.
Keywords: geoinformation methods; modeling; spatio-temporal changes; Chop-Mukachevo basin; groundwater; chemical composition; monitoring; database; security